Interval Elektromekanikal Atrium Menggunakan Doppler Jaringan Sebagai Prediktor Kejadian Fibrilasi Atrium Pasca Operasi Bedah Pintas Arteri Koroner - Ignatius Yansen; Amiliana Mardiani; Poppy S Roebiono (Jurnal Kardiologi Indonesia, 2013)
Background. Atrial fibrillation (AF) is the most common arrhythmia complication in patient undergone coronary artery bypass grafting (CABG) with the incidence of 20-50% according to different studies. Although this complication is temporary but can be life threathening, and increased the number of mortality and morbidity. Thus, it is very important to identified factors that can predict the occurance of AF post CABG. This study use atrial electromechanical interval and interval dispertion as predictor of AF post CABG.Methods. One hundred and eight patients were included in this case control study. Samples were taken consecutively from May to September 2012 among patients with coronary artery disease undergoing CABG at the National Cardiovascular Center Harapan Kita Jakarta. The patients underwent a preoperative transthoracic echocardiography with tissue doppler evaluation. We measured the atrial electromechanical interval in the lateral of left atrium, septal and lateral of right atrium also inter and intra atrial interval dispertion. Patients was monitored thorugh out hospitalization for the occurance of AF.Result. In our study, 27 out of 108 (25%) patients developed AF post CABG. There are 3 independent parameters that can predict AF post CABG. These parameters are electromechanical interval in lateral left atrium, left atrial volume index, and post operative beta blocker. There are longer electromechanical interval in lateral left atrium in patients with AF post CABG (81,12±9,84 ms vs 64,43±13,53 ms, P=0.00). Patients with AF had bigger left atrial volume index (37,31±9,50 ml/m2 vs 30,28±8,19 ml/m2, P=0.037) and more beta blocker post CABG (20 (74,1%) vs 72(88,9%), P=0.026). There are no difference intra and interatrium dispertion of electromechanical interval.Conclusion. The interval of Electromechanical in the lateral left atrium using tissue dopper echocardiography can predict the occurrence of AF post CABG.